1989
DOI: 10.5006/1.3577838
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Oxygen and pH Microelectrode Measurements at Water-Immersed Metal Surfaces

Abstract: Dissolved oxygen (DO) and pH were measured at metal/artificial seawater interfaces using microelectrodes in biotic and abiotic systems. Mesurements in a closed system proved that presence of electrochemical and/or biological reaction products substantially influence the conditions at the metal surface. For long-term studies, only open (e.g., continuous flow) reactors should be used. An open channel flow reactor suitable both for microbiological and electrochemical measurements has been constructed and successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Salgavo et al [8] analyzed alloy 600 (UNS N06600) sample cathodically polarized to −0.8 V to −1.2 V (Ag/AgCl) in natural seawater at temperatures between 13 • C and 27 • C. The probe was 1 mm from the metal surface and the maximum pH value recorded was 10.7 at −1.2 V (Ag/AgCl). Lewandowski et al [12] found pH values between 9.5 and 10 at −1.0 V (SCE) on 304 stainless steel (AISI 304SS) surface in synthetic seawater at room temperature. The distance between the pH microelectrode and the stainless steel surface was not specified.…”
Section: Introductionmentioning
confidence: 99%
“…Salgavo et al [8] analyzed alloy 600 (UNS N06600) sample cathodically polarized to −0.8 V to −1.2 V (Ag/AgCl) in natural seawater at temperatures between 13 • C and 27 • C. The probe was 1 mm from the metal surface and the maximum pH value recorded was 10.7 at −1.2 V (Ag/AgCl). Lewandowski et al [12] found pH values between 9.5 and 10 at −1.0 V (SCE) on 304 stainless steel (AISI 304SS) surface in synthetic seawater at room temperature. The distance between the pH microelectrode and the stainless steel surface was not specified.…”
Section: Introductionmentioning
confidence: 99%
“…Lewandowski et al [73] and Lewandowski [74] used microelectrodes to determine the oxygen concentration around a microcolony. The microcolony was anoxic in the middle, but oxygen was detected at the bottom, demonstrating transport via channels and voids in addition to diffusion.…”
Section: C14 Microsensorsmentioning
confidence: 99%
“…It should be noted from Figure 10 that only the deposits formed by polarization at −0.80 V contained the Mg element. Usually, magnesium hydroxide precipitates in sea water at a critical pH value as high as 9.3 or more [5,44]. This implies that applied polarization at −0.80 V can result in local environment of high pH at the interface of metal and electrolyte, which promotes the deposit of Mg(OH) 2 .…”
Section: Edx Analysismentioning
confidence: 99%